The Anticoagulant Nafamostat Potently Inhibits SARS-CoV-2 S Protein-Mediated Fusion in a Cell Fusion Assay System and Viral Infection In Vitro in a Cell-Type-Dependent Manner - Yamamoto, Mizuki; Kiso, Maki; Sakai-Tagawa, Yuko; Iwatsuki-Horimoto, Kiyoko; Imai, Masaki; Takeda, Makoto; Kinoshita, Noriko; Ohmagari, Norio; Gohda, Jin; Semba, Kentaro; Matsuda, Zene; Kawaguchi, Yasushi; et al. (Viruses, 2020)
Although infection by SARS-CoV-2, the causative agent of coronavirus pneumonia disease (COVID-19), is spreading rapidly worldwide, no drug has been shown to be sufficiently effective for treating COVID-19. We previously found that nafamostat mesylate, an existing drug used for disseminated intravascular coagulation (DIC), effectively blocked Middle East respiratory syndrome coronavirus (MERS-CoV) S protein-mediated cell fusion by targeting transmembrane serine protease 2 (TMPRSS2), and inhibited MERS-CoV infection of human lung epithelium-derived Calu-3 cells. Here we established a quantitative fusion assay dependent on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) S protein, angiotensin I converting enzyme 2 (ACE2) and TMPRSS2, and found that nafamostat mesylate potently inhibited the fusion while camostat mesylate was about 10-fold less active. Furthermore, nafamostat mesylate blocked SARS-CoV-2 infection of Calu-3 cells with an effective concentration (EC)50 around 10 nM, which is below its average blood concentration after intravenous administration through continuous infusion. On the other hand, a significantly higher dose (EC50 around 30 μM) was required for VeroE6/TMPRSS2 cells, where the TMPRSS2-independent but cathepsin-dependent endosomal infection pathway likely predominates. Together, our study shows that nafamostat mesylate potently inhibits SARS-CoV-2 S protein-mediated fusion in a cell fusion assay system and also inhibits SARS-CoV-2 infection in vitro in a cell-type-dependent manner. These findings, together with accumulated clinical data regarding nafamostat’s safety, make it a likely candidate drug to treat COVID-19.